Insider trading and market manipulation : investigating and prosecuting across borders - Austin, Janet, 1958- (Edward Elgar Publishing, 2017)
This book explores how the globalization of securities markets has affected market manipulation and insider trading. It delves into the responses of securities regulators, discussing new regulations designed to deter such misconduct, as well as they ways in which detection, investigation and prosecution techniques are adapting to tackle insider trading and market manipulation that crosses international boundaries. Janet Austin concisely and clearly explains changes to securities markets that have taken place over the last few decades and their impacts, as well as the main detection and investigative techniques of securities regulators. She also provides an analysis of how the work of the International Organization of Securities Commissions (IOSCO) is assisting securities regulators as they gather information and evidence they need in order to prosecute these market offences. The book concludes with suggestions for the IOSCO and securities regulators to improve their efforts in addressing cross-border market manipulation and insider trading, with a view to enhancing the overall integrity of the securities markets. The approachable analysis and hard-to-find information in this book make it a valuable resource for securities regulators, legal practitioners, and academics.